Peterson first guide to rocks and minerals - Pough, Frederick H. (Houghton Mifflin, 1991)
Written and designed for the beginner, this book describes and illustrates the most common and interesting rocks and minerals, from simple sandstone to exotic gems. Illustrated with dozens of beautiful color photographs, it tells how these rocks and minerals formed and how to identify them--and includes tips on collecting.